Combating chloride ions in reinforced concrete using K2Cr2O7 as corrosion inhibitor - Mayowa Ikumapayi, Catherine; Adedamola Adeniji, Akintayo; Osamudiamen Idehen, Emmanuel; Barnabas, Abel Adeiza (جامعة الوادي - university of el oued, 2020)
The ingress of chloride ions from seawater in contact with concrete reinforced structures is one of the major causes of deterioration in the construction industries worldwide. This gives rise to corrosion of embedded steel in the concrete structures which sooner or later results in dilapidation, deterioration and partial or total failure of the reinforced structure. In this study potassium dichromate (K2Cr2O7) solution was used to mitigate the effects of chloride ions in reinforced concrete. Cylindrical concrete samples of size 15mm x 36mm diameter with cement to sand mix ratio of 1:6 and a water cement ratio of 0.5 were prepared. 12 mm high yield reinforcing bars were inserted into the sample. The samples were then immersed in NaCl solution with varying concentration of K2Cr2O7. Both weight loss method and linear polarization measurement were performed on the samples. Data acquisition and analysis were carried out using 4 decimal places electronic weighing balance, a potentiostat interfaced and a computer. The results from the weight loss method showed that the weight loss decreased from 0.7629g to 0.1398g for the 7th and 35th day respectively. Results from the potentiodynamic polarization method further revealed the efficiency of K2Cr2O7 in mitigating corrosion.
Article
Keywords: Corrosion; Chloride ion; linear polarization; Weight loss; Potassium dichromate.